2016
DOI: 10.1097/jnn.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ventilator-Associated Pneumonia in the Intensive Care Unit

Abstract: Ventilated-associated pneumonia (VAP) is a major concern for hospitals and a major problem for ventilated patients in the intensive care unit. Included in the basics are hand hygiene, wearing gloves, endotracheal tube suctioning, head of bed at 30°, stress ulcer prophylaxis, turning patient side to side at least every two hours, and giving the patient a sedation vacation each morning. Beyond the basics included here are oral hygiene, oral suctioning, endotracheal tube cuff pressure, artificial humidification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…However, our study showed adherence of 73,76% and 1,85%, respectively. Larrow and Heartt (2016) confirm that the premature removal of the patient from the bed decreases the risk of incidence of VAP. Li et al (2018) included removing the patient from the bed in his study of implementing a bundle checklist, which remained to obtain positive results.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…However, our study showed adherence of 73,76% and 1,85%, respectively. Larrow and Heartt (2016) confirm that the premature removal of the patient from the bed decreases the risk of incidence of VAP. Li et al (2018) included removing the patient from the bed in his study of implementing a bundle checklist, which remained to obtain positive results.…”
Section: Resultssupporting
confidence: 54%
“…Those authors identified an adherence of 90,99% on this strategy, while our study is compared, with 85,49% of occurrences. Larrow and Heartt (2016) argue that the use of the humidifier filter within the expiration date may be the key to the prevention of VAP.…”
Section: Resultsmentioning
confidence: 99%
“…There are non-VAP bundle factors that impact outcomes such as progressive mobility, ICU sedation, and enteral nutrition that impact nosocomial infections, and we recognize that the implementation of these policy changes may have contributed to the improved VAP rates and mortality documented in this study. 7,13,14 We further recognize that the combination of all of these changes impacted outcomes, as our mortality was positively impacted as well.…”
Section: Discussionmentioning
confidence: 89%
“…The use of disposable airway aids; smooth, non-traumatic airway manipulation, including intubation; and steps to prevent aspiration and irrigation after appropriate neuromuscular recovery is therefore required. Optimal postoperative analgesics are necessary to provide adequate pain relief and avoid excessive sedation [10]. Preoperatively, when there is ciliary dyskinesia, pulmonary status should be managed by chest physiotherapy; infections should be treated, for instance, by antibiotic administration during surgery [5].…”
Section: Discussionmentioning
confidence: 99%
“…As nasal polyps can obstruct the nasal cavity and pharynx, an oropharyngeal airway should be established to assist in preoxygenation before anesthesia induction. Early mobilization and humidification of the inspired gases should assist in the clearance of mucus and may decrease the duration of hospital stay and morbidity [10]. Appropriate pain relief, with early mobilization, postural drainage, and the use of antibiotics, bronchodilators, and oxygenation will decrease the risk of excessive respiratory secretions and intra-operatively acquired infections.…”
Section: Discussionmentioning
confidence: 99%